Impact d'une mixture environnementale d'organochlorés sur l'ovocyte, le spermatozoïde et l'embryon porcin in vitro - Campagna, Céline (Université Laval, 2008)
Human beings and animals, especially those living in the Arctic Circle, are constantly exposed to a wide range of chemical compounds that are present in their environment and food. Among these pollutants, organochlorine compounds are considered as a major group of toxicants that disrupt numerous physiological systems, including the reproductive system. These compounds are rarely present one at a time in the biota; they are mainly present as complex mixtures of different organochlorines, where each compound influences physiological systems in its own way, independently or in concert with other compounds. Organochlorines are present in blood, breast milk, fat tissues, as well as in amniotic, seminal, uterine and ovarian fluids. Therefore, we tested the hypothesis that an organochlorine mixture, reconstituted to mimic that present in the Arctic seal blubber and ingested by the Inuits in Nunavik, disrupts the competence to in vitro maturation, fertilization and development of gametes and embryos, using the pig as a toxicological model for humans. The organochlorine mixture reduced maturation, fertilization and developmental competence of exposed oocytes. It also reduced fertilization and subsequent development of gametes exposed during fertilization, as well as preimplantory development of exposed embryos. We also used a metabolized extract of the same mixture, originating from the serum of sows preexposed to the original organochlorine mixture, to verify the same parameters. The metabolized extract did not reduce oocyte maturation or their competence to fertilization and development; neither did it alter preimplantory development of exposed embryos. Nevertheless, the metabolized extract reduced apoptosis in cumulus cells. In conclusion, the environmentally-relevant organochlorine mixture damages essential functions of gametes and embryos, therefore altering their fertilizing and developmental competence. Les êtres humains et les animaux, principalement ceux habitant le Cercle Arctique, sont constamment exposés à ...